THE DEVELOPMENT OF THE LITERACY OF QUR’ᾹNIC INTERPRETATIONS IN SUDAN: CRITICAL STUDY OF THE AL-TAFSĪR AL-TAUḤĪDĪ - Hasan, Moh Abdul Kholiq (Jurnal At-Tibyan: Jurnal Ilmu Alqur'an dan Tafsir, 2021)
This article aims to critically explain the method of al-Tafsīr al-Tauḥīdī by Ḥasan al-Turābī and its position amongst other thematic commentary theories. This study is a descriptive qualitative study by employing content analysis theory. The results indicate the trend of al-Tafsīr al-Tauḥīdī in two meanings. The first is as a commentary paradigm which leans on the unity of man and the universe in the message of the God’s revelation. The second is as the form of thematic commentary of al-Waḥdah al-Mauḍū‘iyyah model. Therefore, this commentary is more appropriately categorized into al-Tafsīr al-Muṣhafī bi al-Waḥdah al-Mauḍū’iyyah. It has three systematic explanation in each surah including Khulāṣah Hady al-Sūrah, Tartīl al-Ma’āni, and Umūm al-ma’āni. Al-Turābī's ability to unite various related elements in his commentary is not only between verses or surahs but also between human life and all its activities with the universe in a bond of al-Qur'an guidance which is core to monotheism. This is the advantage it has and is a new method in commentary literacy in Sudan. In fact, the method of al-Tafsīr al-Tauḥīdī generally becomes a framework for the whole civilization project of al-Turābī. However, there are some critics towards his commentary regarding rationality and rejection of several authentic hadiths which seem to leave riwāyah in the commentary of the Qur’an.